Antioxidant hydrogels for the treatment of osteoarthritis: mechanisms and recent advances - He, Feng; Wu, Hongwei; He, Bin; Han, Zun; Chen, Jiayi; Huang, Lei (Frontiers in Pharmacology, 2024)
Articular cartilage has limited self-healing ability, resulting in injuries often evolving into osteoarthritis (OA), which poses a significant challenge in the medical field. Although some treatments exist to reduce pain and damage, there is a lack of effective means to promote cartilage regeneration. Reactive Oxygen Species (ROS) have been found to increase significantly in the OA micro-environment. They play a key role in biological systems by participating in cell signaling and maintaining cellular homeostasis. Abnormal ROS expression, caused by internal and external stimuli and tissue damage, leads to elevated levels of oxidative stress, inflammatory responses, cell damage, and impaired tissue repair. To prevent excessive ROS accumulation at injury sites, biological materials can be engineered to respond to the damaged microenvironment, release active components in an orderly manner, regulate ROS levels, reduce oxidative stress, and promote tissue regeneration. Hydrogels have garnered significant attention due to their excellent biocompatibility, tunable physicochemical properties, and drug delivery capabilities. Numerous antioxidant hydrogels have been developed and proven effective in alleviating oxidative stress. This paper discusses a comprehensive treatment strategy that combines antioxidant hydrogels with existing treatments for OA and explores the potential applications of antioxidant hydrogels in cartilage tissue engineering.